Improving the pedagogy of Islamic religious education through an application of critical religious education, variation theory and the learning study model - DEMİREL UÇAN, AYŞE (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This study presents a new theoretical and pedagogical framework based on the theories of Critical Religious Education (CRE), Variation Theory (VT) and the Learning Study model with the purpose of improving teaching and learning in Islamic Religious Education (IRE). It reports a Learning Study conducted in a secondary girls Muslim school in London on the topic of 'Islam and being Muslim'. The aim of this research study is to examine if and how the proposed framework can be applied to IRE lessons, and how it affects the students' learning. Thirty students of two seventh grade classes and their religious education teacher participated in the study. The data was collected through interviews and written tasks with the students before and after their participation in the study, video-recordings of the research lessons, and meetings with the teacher. Phenomenography and VT were utilised in the analysis of the data. The results suggest that the use of CRE, VT and Learning Study in teaching Islam contributes to students' learning outcomes by means of helping teacher consider students' diverse perspectives on religious phenomena when planning and implementing the curricular content, increasing students' awareness of the ontological and epistemological dimensions of their faith as well as allowing them to make informed judgments about religious phenomena.
Keywords: Islamic religious education; critical religious education; variation theory; the learning study model; STUDENTS; KNOWLEDGE; TEACHERS